WORKING IN JAPAN AS A TRAINEE: THE REALITY OF INDONESIAN TRAINEES UNDER JAPAN'S INDUSTRIAL TRAINING AND TECHNICAL INTERNSHIP PROGRAM - NFN Nawawi (Jurnal Kependudukan Indonesia, 2010)
Attracted by Japan's prosperity and motivated by desire for gaining higher income, many Indonesians have been migrating to Japan in increasing numbers since the mid-1990s. Different from other destination countries, most of Indonesian workers who came to Japan is under the program called "Industrial Training and Technical Internship Program" with the main objective to get the use of actual work to obtain new knowledge and technical skills. This paper aims to shows the reality oflndonesian trainees and the issues related to implementation of the training program in Japan. The bulk of empirical data in this paper is drawn from a field study on Indonesian trainees in some big cities in Japan. Primarily, the study includes a questionnaire survey to 120 Indonesian trainees who are working in some factories in Mie Prefecture as well as extended interviews with key informants, field observation and related literature study. This study found that many of the young Indonesians questioned showed that in the reality, the training program is just a way to fulfill Japan's labor shortage and hired as a cheap labor source for small and medium companies in Japan. Further, many of them had discovered that they have to take unproductive jobs where no new skills or technology techniques transfer really take place. Most of them were involved in marginal jobs or assigned to a small part of the operation. However, it is considered that, in spite of many problems in the implementation of the current training program of Japan, as long as the significant difference remains in employment opportunity and earning between Japan and Indonesia, the efforts of dispatching more Indonesians to Japan is still an important policy for both countries.Key words: International Migration, Industrial Training and Technical Internship Program, and Indonesian Trainees in Japan.